Analysis of the role-playing game’s impact in the development of the argumentation from the students of science in A levels - González Sánchez, Erika; Acebal, María del Carmen; Brero-Peinado, Vito Battista (My University, 2019)
Abstract: - The present work belongs to a line of investigation about the design, development and assessment of the role-playing game as an innovative methodological strategy for the teaching of sciences and the environmental education in obligatory and post-obligatory secondary education. The first advances in this line, referred to the design and launch of the role-playing game, were presented in the International University Conference about the communication working and at the university nowadays: CUICIID 2014. Likewise, the preliminary results in relation to the students’ attitudinal change promoted by the role-playing activity, were presented in the edition CUICIID 2015. Continuing with the same line of investigation, this third phase is dedicated to the assessment of the role-playing game as a methodological strategy to promote the development of the scientific competence through the argumentation. Thus, it is focused on the impact of the activity in students’ argumentation process, analysing their written productions before and after their participation in the role-playing game (Pre-Post Test). These written productions include the students’ opinions about the construction of a wind marine park in a coast next to their city (a proposal which was debated in the role-playing activity). Firstly, a methodology based on the Toulmin Model was employed to determine the complexity of the students’ arguments. Then, the arguments given by the students before and after the activity were compared, in order to appreciate a possible development due to the influence of the role-playing game.
Keywords: Enseñanza - Innovaciones; Tecnología educativa; Teaching of sciences; Methodological innovation; Scientific competence; Role-playing game; Argumentation